2003
DOI: 10.1046/j.1468-2982.2003.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity and Specificity of the Case Definition Criteria in Diagnosis of Headache: A School-Based Epidemiological Study of 5562 Children in Mersin

Abstract: The objectives of the present study were to estimate the prevalence of recurrent headaches in schoolchildren (ranging from 2nd to 5th degrees) in Mersin city of Turkey and to determine the sensitivity, specificity, positive predictive value and positive likelihood ratio of the diagnostic headache characteristics in children with migraine and Tension Type Headache (TTH) using neurologist's diagnosis as the gold standard. The stratified sample of study was composed of 5562 children. The prevalence of recurrent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
145
6
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(182 citation statements)
references
References 31 publications
21
145
6
8
Order By: Relevance
“…Surprisingly preschool boys experience highly frequent recurrent headaches more often than girls of this age (boy/girl ratio 10:1). As internationally reported (e.g., Özge et al [8]), further specific influences on pain characteristics by gender or social class have not been detected for our examined sample, being 5-6 years of age.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Surprisingly preschool boys experience highly frequent recurrent headaches more often than girls of this age (boy/girl ratio 10:1). As internationally reported (e.g., Özge et al [8]), further specific influences on pain characteristics by gender or social class have not been detected for our examined sample, being 5-6 years of age.…”
Section: Discussionsupporting
confidence: 48%
“…However, recurrent headache and abdominal pain without organic reasons are the most common pain symptoms in children [2][3][4][5][6][7][8][9][10][11][12]. A high comorbidity between these two aversive syndromes is reported [6,13], which seems to continuously increase over time [2,6,7,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Population-based studies reported that the prevalence of migraine in childhood and adolescence ranges from 3% to 14% [1][2][3][4][5][6]. From the time of Wolff's early portrait of the childhood personality characteristics of migraine patients, the research began to explore the association of headache first with broad personality traits and then with distinct psychiatric symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%